2015
DOI: 10.1155/2015/610813
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of Oxidative Stress and Inflammation in Neurodegenerative Disease: Role of TNF

Abstract: Neuroinflammation and mitochondrial dysfunction are common features of chronic neurodegenerative diseases of the central nervous system. Both conditions can lead to increased oxidative stress by excessive release of harmful reactive oxygen and nitrogen species (ROS and RNS), which further promote neuronal damage and subsequent inflammation resulting in a feed-forward loop of neurodegeneration. The cytokine tumor necrosis factor (TNF), a master regulator of the immune system, plays an important role in the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
360
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 555 publications
(402 citation statements)
references
References 211 publications
14
360
1
8
Order By: Relevance
“…28 The excessive production of reactive oxidative species (ROS) is associated with inflammation, 29 and aged rodents exhibited exaggerated neuroinflammation and memory deficits in response to OS. 30 We found a clear inflammatory landscape in hippocampus in old in comparison with young mice, which could be the…”
Section: Discussionmentioning
confidence: 99%
“…28 The excessive production of reactive oxidative species (ROS) is associated with inflammation, 29 and aged rodents exhibited exaggerated neuroinflammation and memory deficits in response to OS. 30 We found a clear inflammatory landscape in hippocampus in old in comparison with young mice, which could be the…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a significant increase in TNF-α from baseline levels was observed 60 min post-LPS, peaking earlier than the other cytokines measured. TNF-α is a primary proinflammatory marker and plays an important role in the activation and recruitment of immune cells (50). Interestingly, antiinflammatory IL-10 levels also increased from baseline as a possible signaling mechanism to "switch off" M1 and "switch on" M2 microglia to regulate the neuroinflammatory process, as cytokines and sickness symptom levels appeared to be decreasing 1 h into the scan (240 min post-LPS).…”
Section: % At 1 H and 4 H Post-lps (01 Mg/kg) Respectively) (32)mentioning
confidence: 99%
“…It is also characterized in the early stages with defects in inflammation and oxidative stress [1]. Inflammation is especially important as it occurs in pathologically vulnerable regions of AD and can influence AD development.…”
Section: Introductionmentioning
confidence: 99%